PKM LATIHAN KEPEMIMPINAN TINGKAT DASAR BAGI PENGURUS OSIS DAN PENGURUS KELAS SMA NEGERI WELAMOSA - Aurelius Fredimento; Nong Hoban; Gregorius Sebo Bito (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2020)
A leader, in any level, is a main figure to determine a success of the desire of an organization. A leader who attends as an influential resource, an organizer resource, an action resource as well as a directive resource who guide the members to arrange strategic steps, logical and reasonable in order to get the intention of organization that is agreed together. The board of OSIS and the management of the class at the Government Senior Hight School (SMAN) in Welamosa is a collection of the energic young figures who have good competence and self-competence to become a great leader in the future. They are internally considered have specific competence to become leader for they friends, so they are elected as well as determined by the school democratizely to become a leader because they have a certain competence to work together and control the institution education as well. The election is an opportunity which has to be run professionally and responsible. Before starting to run their leadership, it is necessary and important to build them with the basic consepts about the rightist leaderships for the institution in the future. That is why, they have to run a specific activity such as Basic Training Leadership (LKTD). With this activity the whole participants are very expected will be more self awareness about various kinds of self-competence which have been planted in themselves and gradually accordance with the development of biologis, cognitive, affective and also phichomotorics have to try to bring into reality for the importance of the school as well as the societies. This activity uses the reflective analyses method. By this method, the whole participants are invited to see and to take into account the leadership training well and has to try to implementate at school. The analyses method is a very good method to run the school or to manage an education institute well at the Government Senior High School in Welamosa.